PEMBERDAYAAN PENGGERAK PKK MELALUI PENGEMBANGAN KERAJINAN SAMPAH NON-ORGANIK DI DESA SANDIK KECAMATAN BATU LAYAR LOMBOK BARAT - Baiq Ismiwati; Taufik Chaidir; Ida Ayu Putri.S; Siti Sriningsih (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2021)
Zero waste is an ethical, economical, efficient and visionary goal, to guide people in changing their lifestyles and practices in imitation of a sustainable natural cycle, where all materials that are no longer used are designed to be a resource for others to use (en. m.wikipedia.org). Problems related to waste in Sandik Village are: 1. Non-organic waste is relatively widely scattered in the Sandik Village environment; 2. The waste bank is not yet operational; 3. People do not know much about non-organic waste which can be used as raw material for creative products that have a selling value; 4. The Sandik Village PKK Team does not have the skills to process non-organic waste into handicraft products with economic value. The aim of this service is to empower the Sandik Village PKK Driving Team in processing non-organic waste into goods that have economic value. The service method is carried out with lectures, discussions, and technical training on processing non-organic waste into products with sale value. The results of the activity: there were several participants who were able to make products at the end of the training; Participants were willing and enthusiastic to pass it on to other mothers around the village. It can be concluded that this service activity was successful, as shown by: Participants were able to sort between organic and non-organic waste and increased participants' knowledge about some of the non-organic waste that they produce every day can be used and processed into useful and economic value items